Hot Water and Sulfuric Acid Solution for Increasing The Viability and Vigor of Indigofera (Indigofera zollingeriana). Issue 1 (March 2020) - Fahmi, Z I; Purwanto, E; Purnomo, D
Abstract: Indigofera ( Indigofera zollingeriana ) is a multi-benefit plant, two of them are for natural dyes and livestock feed supplement. Indigofera seeds are hard and thick-coated so that the germination percentage is low and not grow in simultaneously. This study aimed to obtain an effective and practical method of increasing seed viability and vigor was carried out from March to May 2019 at the BBTP Central Java. The research used a completely randomized design, consisted 9 treatments(control, soaked in hot water by 80 and 100°C then leave it for 24 hours, and soaked in a solution of H2 SO4 95% for 10, 20, 30, 40, 50 and 60 minutes) and 4 replications. The germination method used the top of paper with filter paper media. The results showed that soaking the seeds in hot water and sulfuric acid solutions significantly increased germination, maximum growth potential, vigor index, and growth rate. Soaking seeds in a 95% H2 SO4 solution for 10 minutes increased the germination of the seeds (84%), maximum growth potential (91%), vigor index (69%), and growth rate by (13.81% etmal −1 ). The finding concludes that the best treatment was soaking seed in H2 SO4 solution for 10 minutes, and longer soaking time (> 50 minutes) will decrease all parameters.